Awareness of Loan Defaulters of LAMPS about Membership and Loans : A Review - Senthil, S.; Thiruniraiselvi, D. (Arthshastra Indian Journal of Economics & Research, 2022)
The study assessed the level of awareness, particularly about membership and loans, of loan defaulters among scheduled tribe members of large-sized multi-purpose cooperative societies. The research was conducted in two of the five large area multi-purpose societies (LAMPS) functioning in Salem district in Tamil Nadu. A structured interview schedule was prepared to collect data from 187 defaulters, and the analysis was done with chi-square as a core statistical tool. The results showed that the level of awareness among the respondents toward their membership and loans differed considerably. Awareness was high among males (38.90%), followed by those with an education qualification of at least higher secondary (34.10%) ; whereas, in terms of occupation, farmers (47%) showed considerable awareness. While 40.60% of the respondents who had an annual family income between INR 2 lakhs – 3 lakhs had awareness, the highest level of awareness was seen among the respondents holding more than 3 hectares of agricultural land (87.50%). The level of awareness was found to have a positive correlation with social status and repayment of loans; whereas, it was negative when defaults were high. Non-payment of loans threatens the very purpose of the existence of LAMPS and should be regulated through valid measures of LAMPS and voluntary initiatives of members.